On the uniformity of distribution of Farey fractions - Stakėnas, Vilius (Lietuvos matematikos rinkinys, 2009)
Let F x be the set of nonnegative rationals m with 0 < n < x and (m, n) = 1. For some fixed interval I ⊂ (0;+∞), I = (λ1;λ2) let F (u|x, I) = #(Fx ∩ (λ1;λ1 + u(λ2 - λ1))/#(Fx ∩ I). The paper deals with the estimation of discrepancy |F (u|x, I) - u|, 0 < u < 1.